Colorectal Cancer in African Americans: An Update: Prepared by the Committee on Minority Affairs and Cultural Diversity, American College of Gastroenterology. Issue 7 (July 2016) - Williams, Renee; White, Pascale; Nieto, Jose; Vieira, Dorice; Francois, Fritz; Hamilton, Frank
Abstract : N/A: This review is an update to the American College of Gastroenterology (ACG) Committee on Minority Affairs and Cultural Diversity's paper on colorectal cancer (CRC) in African Americans published in 2005. Over the past 10 years, the incidence and mortality rates of CRC in the United States has steadily declined. However, reductions have been strikingly much slower among African Americans who continue to have the highest rate of mortality and lowest survival when compared with all other racial groups. The reasons for the health disparities are multifactorial and encompass physician and patient barriers. Patient factors that contribute to disparities include poor knowledge of benefits of CRC screening, limited access to health care, insurance status along with fear and anxiety. Physician factors include lack of knowledge of screening guidelines along with disparate recommendations for screening. Earlier screening has been recommended as an effective strategy to decrease observed disparities; currently the ACG and American Society of Gastrointestinal Endoscopists recommend CRC screening in African Americans to begin at age 45. Despite the decline in CRC deaths in all racial and ethnic groups, there still exists a significant burden of CRC in African Americans, thus other strategies including educational outreach for health care providers and patients and the utilization of patient navigation systems emphasizing the importance of screening are necessary. These strategies have been piloted in both local communities and Statewide resulting in notable significant decreases in observed disparities.